Le Congrès culturel de La Havane (1968) : point de bascule de l’engagement français envers la révolution cubaine - Rafael Pedemonte (Revue Internationale des Études du Développement)
Based on unpublished primary sources (private collections, diplomatic archives, interviews), this article examines a key moment for French commitment to Cuba’s revolutionary project: the Cultural Congress of Havana of January 1968, an international conference that gathered around 500 foreign guests, including nearly 80 French intellectuals. The “Third Worldist” inclination of the Cuban Revolution and its ideological defiance to the USSR was keenly welcomed by many French people, who saw in Cuba the emergence of a non-dogmatic revolutionary model focused on South-South solidarity, and freedom of thought and creation. Back in France, many participants in the congress implemented concrete initiatives in support of the Cuban Revolution, but the events of May 1968 and Castro’s backing of the military intervention in Czechoslovakia (August 1968) dampened this militant momentum, obstructing French solidarity projects towards Cuba.